Impact of various surface treatments on the shear bond strength between lithium disilicate ceramics and resin cement - Alrabeah, Ghada; Alhamid, Reem F.; Alamer, Buthainah A.; Alrajhi, Farah N.; Binrayes, Abdulaziz; Habib, Syed Rashid (Frontiers in Materials, 2024)
Pre-etching ceramic restorations in dental laboratories is preferred by numerous dentists due to the potential health concerns associated with handling hydrofluoric acid (HF) if not managed correctly. This study aimed to evaluate the effect of different surface treatments on the shear bond strength (SBS) between lithium disilicate ceramics and self-adhesive resin cement. For this study, a total of 60 IPS e. max CAD (Ivoclar Vivadent) lithium disilicate specimens were prepared. Specimens were randomly divided into six groups, with 10 specimens per each. Different surface treatments were applied (1: Control group no surface treatment (C); 2: 10% hydrofluoric with silane coupling agent (HFS); 3: 10% hydrofluoric acid only (HF); 4: Sandblasting with 50 μm aluminum-oxide powder (AO); 5: Sandblasting with 30 μm silica-coated aluminum-oxide powder (SC), and 6: Er,Cr:YSGG laser (L). SBS tests were performed, and data analyzed using one-way ANOVA and Tukey’s multiple comparisons. The difference between the mean average of SBS was statistically significant among all different surface treatments (p ≤ 0.05) except for the L group with a (p = 1.00). The highest mean value was observed in the HFS followed by the HF group. Whereas the L group showed no statistical significance in comparison with the C group (p > 0.05). Hydrofluoric acid etching in combination with a silane coupling agent was the most effective surface treatment for bonding lithium disilicate ceramics with resin cement. In contrast, laser irradiation was the least effective among all other groups.